More Power, More Warmth: The Enhancing Effect of Power on the Perceived Warmth About High-Power Individuals Under Chinese Culture - Li, Minyan; Yang, Feng; Han, Yang (Frontiers in Psychology, 2022)
Previous literature concerning power stereotypes demonstrates that compared to low-power (LP) individuals, high-power (HP) individuals tend to be perceived as having positive competence but negative warmth. Based on previous research, the current research further classified HP into senior and junior HP and mainly compared the perceived warmth between senior and junior HP individuals in Chinese culture. By classifying power into HP and LP, the pilot study employed the trait-rating task to replicate the results of previous research. In Study 1, we classified HP into senior and junior HP and revealed that participants indicated more positive warmth evaluations for senior HP individuals than for junior HP individuals. We named this “more power, more warmth” effect the MPMW effect. Further investigation demonstrated that the MPMW effect was more likely to emerge for participants with high Confucianism identification (Study 2a), for Chinese participants rather than Western participants (Study 2b), or when the knowledge of Confucianism was accessible in a given situation (Study 3). The present research firstly demonstrated that the contents of power stereotypes may partially display culture-specific characteristics in Chinese culture. The continuous classification approach to power provided a novel insight for future power research.